Unsettling protracted displacement: connectivity and mobility beyond 'Limbo'. Issue 18 (18th October 2022) - Etzold, Benjamin; Fechter, Anne-Meike
ABSTRACT: Conventional understandings of protracted displacement are limited by a number of shortcomings. They imply the stasis of protracted situations; the passivity and disconnection of vulnerable groups who need external support; and immobility of people 'stuck' in places. Moreover, solutions to protracted displacement are based on the priorities of states and defined by the perspectives of humanitarian organisations. In contrast, this special issue seeks to advance scholarly and policy debates in order to advocate for more nuanced understandings and genuinely supportive practices of refugees and internally displaced persons (IDPs). This is realised through the framework of social figurations of displacement, documenting how these evolve over time, and highlighting the structural forces that perpetuate conditions of displacement. Articles in this special issue demonstrate the agency, resilience and transformative power that lies in displaced persons' everyday practices. They foreground the role of multiple mobilities in displacement situations, unsettling the politicised concept of protracted displacement as an example of governance techniques that are geared towards locking the lives of forcibly displaced people in space and in time, rendering the displaced populations controllable. Recognising their mobility and connectivity can become a basis to continuously circumventing and challenging these.